2009
DOI: 10.1038/cdd.2009.169
|View full text |Cite
|
Sign up to set email alerts
|

Control of granzymes by serpins

Abstract: Although proteolysis mediated by granzymes has an important role in the immune response to infection or tumours, unrestrained granzyme activity may damage normal cells. In this review, we discuss the role of serpins within the immune system, as specific regulators of granzymes. The well-characterised human granzyme B-SERPINB9 interaction highlights the cytoprotective function that serpins have in safeguarding lymphocytes from granzymes that may leak from granules. We also discuss some of the pitfalls inherent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 102 publications
(132 reference statements)
2
76
0
1
Order By: Relevance
“…43 Serpin Family C Member 1 (SERPINC1), also known as Antithrombin III, is a known inhibitor of T cell-derived Granzyme A. 44,45 The reproducible PID-enriched amplification of these genes suggests the possibility that amplification of one or more of these genes, alone or in combination, may play a functional role in immune escape that contributes to the immunologically cold phenotype of the PID immune subclass.…”
Section: Discussionmentioning
confidence: 99%
“…43 Serpin Family C Member 1 (SERPINC1), also known as Antithrombin III, is a known inhibitor of T cell-derived Granzyme A. 44,45 The reproducible PID-enriched amplification of these genes suggests the possibility that amplification of one or more of these genes, alone or in combination, may play a functional role in immune escape that contributes to the immunologically cold phenotype of the PID immune subclass.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, the catalytic activity of Grs and other serine proteases is inhibited by serine protease inhibitors or serpins (81). Inhibition occurs through proteolytic attack of the serpin by the Grs, after which a covalent bond is formed between the serpin and the active site of Gr (81). Enzyme/serpin complexes are subsequently removed from the circulation by the liver.…”
Section: Unresolved Questionsmentioning
confidence: 99%
“…Another question is whether extracellular circulating Grs are active, or whether their activity is reduced due to binding by protease inhibitors. In vivo, the catalytic activity of Grs and other serine proteases is inhibited by serine protease inhibitors or serpins (81). Inhibition occurs through proteolytic attack of the serpin by the Grs, after which a covalent bond is formed between the serpin and the active site of Gr (81).…”
Section: Unresolved Questionsmentioning
confidence: 99%
“…As discussed in the review by Kaiserman and Bird, 10 although inhibitors have been identified for some granzymes, surprisingly little is known pertaining to any pathophysiological role for granzyme serine protease inhibitors (serpins) in disease. Much research needs to be done to verify whether they inhibit granzymes in vivo and whether alterations in their regulation, levels, and/or activity are altered in disease.…”
mentioning
confidence: 99%